2014
DOI: 10.1364/josab.31.002565
|View full text |Cite
|
Sign up to set email alerts
|

Laser resonator modeling by field tracing: a flexible approach for fully vectorial transversal eigenmode calculation

Abstract: In this work we generalize the scalar Fox and Li algorithm for the dominant transversal resonator eigenmode calculation to a fully vectorial field tracing concept. Therefore we reformulate Fox and Li's scalar integral equation to a set of coupled operator equations. The introduction of a field tracing round trip operator concept shows that, in principle, any modeling technique which can be formulated to operate for electromagnetic fields can be used to simulate light propagation through the different subdomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In our recent work [27] we have shown that the fundamental mode of any kind of laser resonator can be calculated by the fully-vectorial Fox and Li algorithm. The main idea is that an electric field given at an arbitrary plane inside the resonator must reproduce itself after propagating once through the hole resonator.…”
Section: Generalization Of the Fox And LI Algorithmmentioning
confidence: 99%
See 4 more Smart Citations
“…In our recent work [27] we have shown that the fundamental mode of any kind of laser resonator can be calculated by the fully-vectorial Fox and Li algorithm. The main idea is that an electric field given at an arbitrary plane inside the resonator must reproduce itself after propagating once through the hole resonator.…”
Section: Generalization Of the Fox And LI Algorithmmentioning
confidence: 99%
“…Please note that the remaining electric field component E z and the three magnetic components H x , H y , H z can be calculated from V 1 and V 2 on demand by Maxwell's equations [28]. The propagation of the field through the resonator is described by the resonator round trip operator R. This round trip operator consists of a sequence of approximated or rigorous component operators C m and free space operators P m,m−1 for different subdomains m of the resonator [27]: The transversal resonator mode can be calculated in a arbitrary plane using a sequence of diverse component operators C and free space propagation operators P describing a full resonator round trip. Each operator solves Maxwell's equations in a rigorous or approximated manner for a single subdomain of the resonator.…”
Section: Generalization Of the Fox And LI Algorithmmentioning
confidence: 99%
See 3 more Smart Citations